Promoting Cultural Humility by Integrating Health Equity Literature into the Pharmacy Curriculum - Vincent J. Venditto; Kristie Colón (MDPI AG, 2022)
Strategies that introduce students to unconscious bias and social determinants of health (SDOH) are critical to develop them as effective health care providers. We developed a semester-long activity that utilizes disease-relevant scientific literature to implement cultural humility training in a second-year rheumatology pharmacy course. Students were first re-introduced to implicit bias and then completed an anonymous survey at the beginning and conclusion of the course using a 5-point Likert scale to assess their perceptions of the role of biases and SDOH in patient care. Throughout the semester, five journal articles were assigned that relate to course material and focus on one characteristic (e.g., gout-gender). Students' evolved perceptions of SDOH were compared to baseline data and characteristics of assigned articles indicate an improved understanding of SDOH including race/ethnicity (3.0 to 4.4, p < 0.0001); gender (2.8 to 4.0, p < 0.0001); and religion (2.3 to 2.9, p < 0.01). Among characteristics that were not directly discussed in the assignments, only education showed a significant increase (3.0 to 3.6, p < 0.01). Scientific articles that focus on health inequities relevant to course-specific diseases provide a strategy to integrate discussions that help students evaluate their biases and SDOH with the goal of improving patient care.